2013
DOI: 10.1007/s13595-013-0328-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and environment: two factors related to autumn cold hardiness on Persian walnut (Juglans regia L.)

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Consistent with our hypotheses, provenances of J. cinerea from colder areas (lower hardiness zones) exhibited greater cold tolerance than those from warmer areas when assessed by EL in current-year twigs. This result was similar to that reported for Persian walnut (Juglans regia L.), where individuals from colder provenances sustained less damage following cold treatments (Guàrdia et al 2013) and performed better on colder sites (Hemery et al 2005) than individuals from warmer provenances. Similar results have also been reported in other species, such as white ash (Fraxinus americana L.; Alexander et al 1984) and maritime pine (Pinus pinaster Aiton; Corcuera et al 2011).…”
Section: Cold Tolerancesupporting
confidence: 88%
“…Consistent with our hypotheses, provenances of J. cinerea from colder areas (lower hardiness zones) exhibited greater cold tolerance than those from warmer areas when assessed by EL in current-year twigs. This result was similar to that reported for Persian walnut (Juglans regia L.), where individuals from colder provenances sustained less damage following cold treatments (Guàrdia et al 2013) and performed better on colder sites (Hemery et al 2005) than individuals from warmer provenances. Similar results have also been reported in other species, such as white ash (Fraxinus americana L.; Alexander et al 1984) and maritime pine (Pinus pinaster Aiton; Corcuera et al 2011).…”
Section: Cold Tolerancesupporting
confidence: 88%
“…During the cold-acclimation of plants an accumulation of secondary metabolites, including TP was reported by Cansev et al (2012) and Pennycooke et al (2005). Our interesting results with P. aureosulcata f. aureocaulis in which TP values immediately rose after exposure to low temperatures in October, while the other taxa produced high values only later in November, could be explained by the different freeze tolerance of these species, P. aureosulcata being the most freeze tolerant of the four taxa (Ohrnberger, 2002), and also by possible inter/intraspecific differences in responsiveness to low temperature exposure during cold-acclimation as reported for other plants (Li et al, 2002;Li et al, 2005;Guárdia et al, 2013). Previous available studies on bamboos have not attempted to find reasons for seasonal changes in TP, only defined the period of the year optimal for harvest of bamboo leaves rich in TP.…”
Section: Discussionmentioning
confidence: 67%
“…During the dormancy period the trees may endure temperatures as low as minus 25 or 28 °C with little damage (Szentiványi 1978), but studies made by Fady et al (2003) indicated that early spring frosts may injure the apical buds, or in more severe cases, the ends of young shoots. A close correlation was detected between frost tolerance and origin (Guàrdia et al 2013). Although differences in the frost tolerance of species and cultivars can be attributed to genetically inherited traits, frost tolerance is not a static phenomenon, but exhibits constant changes.…”
Section: Introductionmentioning
confidence: 62%
“…It is difficult to compare the present results with earlier data, as those available were obtained at different locations for different cultivars. Based on the results obtained with various methods, however, it can be concluded that the frost tolerance of the overwintering organs constantly changes and that both genotypic and environmental factors play a role in hardening and dehardening processes, resulting in considerable differences between the cultivars (Aslamarz et al 2010a;Aslamarz et al 2010b;Charrier et al 2013;Guàrdia et al 2013;Charrier et al 2018). The data recorded by Aslamarz et al (2010a) in plantations in the neighborhood of Teheran showed 'Pedro' to be the most frost-tolerant of the cultivars, indicating that, under diverse climatic conditions, the same cultivar may give quite different results.…”
Section: Frost Tolerance Of Hungarian-bred Walnut Cultivarsmentioning
confidence: 99%